1965
DOI: 10.1136/jcp.18.5.611
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous free and bound radioactive vitamin B12urinary excretion test

Abstract: sYNoPsis The absorption of vitamin B12 following the simultaneous administration of 58Co B12 and a complex of 57Co B12 with human gastric juice was assessed by measurement of urinary excretion of radioactivity. Sixteen control subjects, 13 patients with pernicious anaemia, and four who had had total gastrectomy were studied. The method proved a reliable means of detecting those with intrinsic factor deficiency.The urinary excretion test introduced by Schilling (1953) for assessing the absorption of vitamin B12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1969
1969
1983
1983

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…In the previous study [2] all normals indicated a 57Co/58Co ratio of less than 1.6, while all those with PA, gave a ratio greater than 2.0. The results of studying a larger group of patients seem to indicate a slight overlap between the normal and pathological ranges, the range for patients with PA being 1.7 to 9.6, and for the control group 0.8 to 1.8.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In the previous study [2] all normals indicated a 57Co/58Co ratio of less than 1.6, while all those with PA, gave a ratio greater than 2.0. The results of studying a larger group of patients seem to indicate a slight overlap between the normal and pathological ranges, the range for patients with PA being 1.7 to 9.6, and for the control group 0.8 to 1.8.…”
Section: Discussionmentioning
confidence: 69%
“…Since 67Co emits y rays with energies of 0.12 MeV compared with 68Co which emits y rays with energies of 0.81 MeV the amount of each isotope in the total urine collection can be readily determined by altering the discriminator bias settings on an associated scaler, and solving the simultaneous equations described by V eall and V etter [7], for the assay of a liquid containing a mixture of two radioisotopes. The series includes 29 patients whose results were previously published [2]. The patients included in the pernicious anaemia group showed a clinical picture con sistent with the diagnosis supported by the finding of most of the following abnormalities : a macrocytic peripheral blood picture, a megaloblastic bone marrow, a low scrum B,2 level, a histamine fast achlorhydria or a satisfactory response to B12 therapy.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…The bound : free ratio of plasma radioactivity did not exceed 1.6 in any normal subject, and this has, therefore, been accepted as the upper Measurement of plasma radioactivity in vitamin B12 absorption stud ies is well documented [4,6] and the diagnostic value of this test has be come established in recent years. Bell et al [2] and B ell and L ee [3] described a test, based on the method of K atz et al [9], which com bined the two stages of the urinary excretion (Schilling) test. The basis of this test is the simultaneous administration of radioactive Co-labelled vitamin B I2 in 2 isotopic forms, one of which is 'free' while the other is 'bound' to normal human gastric juice.…”
Section: Resultsmentioning
confidence: 99%